THE DEVELOPMENT OF DIGITAL COMPETENCES. CURRENT CHALLENGES AND PERSPECTIVES - Mirela Elena ALEXANDRU; Andreea-Diana SCODA (National Centre for Policy and Evaluation in Education, 2020)
The current context determined by the social distancing has changed the way of carrying out the learning activities which are taught and evaluated at school; during this situation the Romanian and also the global education system faced an unprecedented challenge, namely the transfer of the whole school activity to the online environment. Given this situation, we analyzed data from national and international studies in order to have an overview of the characteristics of digitization and existing digital skills, especially in the Romanian education system. This analysis allowed the understanding of the structure on which this sudden digitization developed and the premises of public policies on which the process was built. The analysis was combined with the presentation of projects carried out during this period, in order to prepare the various school actors in the field of digital education in the form of recommendations to support the empowerment processes in training digital skills of teachers and students in the current context and on a long-term.